Efficacy of supplementation of ?-amylase-producing bacterial culture on the performance, nutrient use, and gut morphology of broiler chickens fed a corn-based diet - Onderci, M; Şahin, Nurhan; Şahin, Kazım; Cikim, G; Aydin, A; Ozercan, I; Aydin, S (Elsevier, 2006)
A trial was conducted to evaluate the efficacy of an Escherichia coli strain producing alpha-mylase of Bacillus stearothermophilus on growth performance, nutrient use, and the morphology of the small intestine of broilers fed a corn-based diet. One hundred thirty-five 1-d-old chicks (Cobb 500) were randomly divided into 3 groups and treated as follows: (i) basal diet (control); (ii) basal diet and water supplemented with an E. coli strain that produced amylase, and (iii) basal diet and water supplemented with an E. coli strain that produced amylase plus bacterial hemoglobin. At 21 d of age, supplementation of E. coli improved daily gain (P < 0.05) and feed conversion (P < 0.01). At the end of the trial, birds supplemented with water containing bacteria consumed more and grew faster (P < 0.05) and had better feed conversion (P < 0.10) than broilers given no bacteria. Also, the presence of bacteria improved apparent digestibility of organic matter (P < 0.01). However, no effects were detected for CP or fat digestibility. Supplementation with E. coli reduced relative pancreas weight (P = 0.06) but did not affect the weight of the liver (P > 0.05) and length of duedonum, jejunum, ileum, and cecum (P > 0.05). Length of the villi and crypts were significantly increased with bacterial supplementation. Presence of the bacterial hemoglobin gene did not cause a significant difference in changes observed. The data indicated that supplementation of an E. coli strain capable of producing alpha-amylase improved digestibility of nutrients and performance of broilers fed a corn-based diet.
Keywords: broiler; Escherichia coli; amylase; digestibility; gut morphology